Pertanggungjawaban Perusahaan yang Mempekerjakan Tenaga Kerja Asing yang Melanggar Izin Kerja di Indonesia Berdasarkan Peraturan Perundang-Undangan - Sonnenora, Wasys Paskah; Kurniawan, Shelly (Syntax Literate, 2023)
Recognizing the fact that the quality of Indonesia's human resources (HR) is still relatively low when compared to other Asian countries, it encourages companies to bring in foreign workers (TKA) to fill a certain field of work that cannot be done by Indonesian workers (TKI), so companies can innovate and meet market demand. Behind the benefits of using foreign workers, Indonesia is faced with the problem of foreign workers who violate the permits that are applied to be able to work in Indonesia. This paper aims to examine the responsibility of companies as guarantors for foreign workers and immigration rules with facts on the ground after seeing that there are still many foreign workers (TKA) violating work permits due to the lack of responsibility of companies as guarantors for foreign workers (TKA). ). This research is a normative juridical law research using secondary data obtained through literature study which is connected with the results of studying the problem which is seen as additional data. The assessment is done deductively. The results of the study identified several problems regarding that there are still companies employing foreign workers who do not comply with the permits and procedures regulated in existing laws and regulations, there is a possibility that the supervisory system and sanctions that have been imposed have not run optimally. For this reason, Indonesia needs to reform the system related to the entry of foreign workers to be able to live and become workers in Indonesia.